2003
DOI: 10.1016/s0304-3959(02)00450-5
|View full text |Cite
|
Sign up to set email alerts
|

A cannabinoid agonist differentially attenuates deep tissue hyperalgesia in animal models of cancer and inflammatory muscle pain

Abstract: Pain associated with cancer and chronic musculoskeletal disorders can be difficult to control. We used murine models of cancer and inflammatory muscle pain to examine whether the cannabinoid receptor agonist WIN55,212-2 reduces hyperalgesia originating in deep tissues. C3H/He mice were anesthetized and implanted with osteolytic NCTC clone 2472 cells into the humeri or injected with 4% carrageenan into the triceps muscles of both forelimbs. At the time of peak hyperalgesia, WIN55,212-2 (1-30mg/kg) or vehicle wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 71 publications
4
60
0
1
Order By: Relevance
“…Endocannabinoids are also involved in endogenous pain inhibition (Walker et al, 2001), as shown in models of chronic inflammatory and neuropathic pain (Agarwal et al, 2007;Bishay et al, 2010). Local injections of cannabinoid receptor agonists reduce pain in various rodent models (Agarwal et al, 2007;Kehl et al, 2003;Lozano-Ondoua et al, 2010). A few human studies also demonstrated a decreased sensitivity and increased tolerance to pain in a THC dose-dependent manner (Cooper et al, 2013;Greenwald and Stitzer, 2000), which is in line with the observation of reduced coupling between thalamus and S2 as the lateral spinothalamic tract is critical for the sensorydiscriminative processing of pain (Maihofner et al, 2006;Price, 2002).…”
Section: Intrinsic Connections (A Parameter)mentioning
confidence: 52%
“…Endocannabinoids are also involved in endogenous pain inhibition (Walker et al, 2001), as shown in models of chronic inflammatory and neuropathic pain (Agarwal et al, 2007;Bishay et al, 2010). Local injections of cannabinoid receptor agonists reduce pain in various rodent models (Agarwal et al, 2007;Kehl et al, 2003;Lozano-Ondoua et al, 2010). A few human studies also demonstrated a decreased sensitivity and increased tolerance to pain in a THC dose-dependent manner (Cooper et al, 2013;Greenwald and Stitzer, 2000), which is in line with the observation of reduced coupling between thalamus and S2 as the lateral spinothalamic tract is critical for the sensorydiscriminative processing of pain (Maihofner et al, 2006;Price, 2002).…”
Section: Intrinsic Connections (A Parameter)mentioning
confidence: 52%
“…[44] Kehl et al found that the antinociceptive effects of systemic cannabinoids on osteolytic sarcoma induced nociception were mediated via CBr1. [21] CBr1 are expressed at central and peripheral nerve terminals and in keratinocytes after being synthesized in DRG. [16] However, only peripheral CBr1 on nociceptors contribute to antinociception in inflammatory and neuropathic pain models.…”
Section: Discussionmentioning
confidence: 99%
“…[21] We tested whether a local CBr2 agonist produces antinociception. Our findings suggest that a peripheral CBr2 agonist could provide relief for cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In preliminary studies, THC produced analgesia equivalent to that of codeine in patients with cancer pain (Noyes et al, 1975). Using a murine model of bone cancer pain, we found that a cannabinoid (WIN 55,212-2) attenuated (~50%) deep-tissue hyperalgesia produced by implantation of fibrosarcoma cells into the humerus (Kehl et al, 2003). The aim of this study was to determine if a more potent cannabinoid, CP 55,940, attenuates tumor-evoked cutaneous mechanical hyperalgesia in a well-characterized murine model of cancer pain.…”
Section: Introductionmentioning
confidence: 99%